Arbetsterapeutiska interventioner och dess effekt för barn med inlärningssvårigheter : En litteraturöversikt - Pettersson, Ulrica; Vestin, Erika (2014)
The purpose of this literature review was to describe Occupational Therapy interventions that are made for children with learning difficulties and their effects. The authors chose to do a literature review of quantitative articles so that the effect of the intervention would be assessed and described. The literature search was conducted in five databases by Luleå University of Technology library and resulted in eleven selected articles. The authors used a grid for analysis of the interventions that were based on Fisher's (2009) practice models. Results of the literature review showed that compensation, activity training and improvement of body functions or personal factors were strategies that occupational therapists used for planning and implementation of interventions. Interventions that develop writing and reading skills have been shown to be common interventions for children with learning difficulties. Three of the eleven interventions showed a significant effect, and the other interventions showed improved abilities in children with learning difficulties. The authors found no research from Sweden investigating the effect of interventions for children with learning difficulties. The authors concluded that research is needed in this area in Sweden to investigate which interventions are made and whether they have any effect for children with learning disabilities in Sweden. Validerat; 20140612 (global_studentproject_submitter)